Crystal Growth and Ferroelectric Properties of Thiourea Picrate Single Crystal - Shanthi, A.; Vella Durai, S.C. (Physics and Chemistry of Solid State, 2024)
Ferroelectric hysteresis (P-E) loop study strongly confirmed that Thiourea Picrate (TUP) crystal is a new lead free, prolific ferroelectric material and good switching behavior of the polarization. Curie phase transition at 70OC was observed in the dielectric analysis and AC conductivity study followed the power law with frequency depended. The elemental composition and surface morphology of the TUP crystal were investigated by EDX and SEM analysis. The thermal behavior of the TUP crystal was analyzed using TG/DTA, and found that the melting point of the prepared crystal was 155 ℃. The photoluminescence study shows TUP has a Blue Emission Property.